Exploring CSR Influence on Financial Performance through Customer Loyalty and Brand Equity: Case of Pakistan’s Banking Industry (Journal of Social Sciences Review, 2025)
The study examines the way CSR affects the bank’s financial performance in Pakistan and investigates whether customer loyalty and brand equity mediating role. For this study, data were gathered through a quantitative design, involving 300 bank customers, including i.e. ABL, Meezan & MCB, customers via a questionnaire, and the past five years of CSR outlays each bank released (2019 to 2024). To collect information, measurement Scales from established works on CSR, financial performance, customer loyalty, and brand equity, and the results were analyzed using SEM. The findings revealed that CSR influenced financial performance (β = 0.42). Moreover, brand equity (β = 0.48) is the stronger mediator, followed by customer loyalty (β = 0.31). These findings reveal that CSR helps a business make more money, not just by boosting its earnings, but also by improving how customers look at the company’s brand and making them more loyal. As a result of this study, banking executives and policymakers should focus CSR efforts on what stakeholders want and incorporate them into the company’s main business approaches. Putting attention on global CSR guidelines, community-based events, and clear reviews by independent auditors encourages customers to trust the brand and keep the company financially stable. The study adds knowledge to existing research by showing that stakeholder and resource-based view theories are useful in a new market, and CSR can truly benefit business.
Keywords: CSR; Financial Performance; Customer Loyalty; Brand Equity; Banking Sector; Pakistan